Virtual quad zygoma implant placement using cone beam computed tomography: sufficiency of malar bone volume, intraosseous implant length, and relationship to the sinus according to the degree of alveolar bone atrophy. Issue 2 (February 2018) - Bertos Quílez, J.; Guijarro-Martínez, R.; Aboul-Hosn Centenero, S.; Hernández-Alfaro, F.
Abstract: The objective of this study was to investigate the malar bone volume and length that a zygomatic implant can engage, and the relationship to the sinus according to the degree of alveolar bone atrophy. A three-dimensional evaluation was performed using cone beam computed tomography scans from 23 patients with a totally edentulous maxilla; quad zygoma implants were virtually placed. The predictor variable was the amount of malar bone volume and length that a zygomatic implant can engage. The primary outcome variable was the relationship to the sinus according to the degree of alveolar bone atrophy. Other variables were the residual alveolar bone height to the floor of the sinus and the nasal cavity. The mean volume of malar bone engaged in this sample of 92 zygomatic implants was 0.19 ± 0.06 cm 3 . The implant had an extrasinus path in 60.9% of cases, a parasinus path in 25%, and an intrasinus path in 14.1%. The results suggest that the average volume of malar bone engaged by a zygomatic implant is constant regardless of implant position and the degree of alveolar bone atrophy. As alveolar atrophy increases, the trajectory of the implant becomes more parasinus and intrasinus. The examiners were able to find enough bone to adequately distribute the implants in all cases.